Kadar Serat dan Tekstur Kue Kembang Goyang dengan Substitusi Beras Merah Organik: Penentuan Formulasi Kue Kembang Goyang Hasil Substitusi Tepung Beras Merah Organik Berdasarkan Kadar Serat Pangan dan Tekstur - Nuri Arum Anugrahati; Clarissa Dian Purnama Sari (Universitas Airlangga, 2023)
Background: The kembang goyang snack has relatively good nutritional content but is considered to have less fiber. This has prompted efforts to substitute white rice flour, the main ingredient of kembang goyang snack, with red rice flour, which has higher fiber content. Objectives: The research objective was to determine the best formulation of the kembang goyang snack based on dietary fiber content and texture. Methods: The study was divided into two stages, the production of red rice flour (organic and non-organic) and the making of kembang goyang snack using various ratios of organic or non-organic red rice flour and white rice flour (0:100; 20:80; 40:60; 60:40; and 80:20). The analysis parameters included yield, moisture content, dietary fiber content, resistant starch content, and texture. The study was designed using a Completely Randomized Design, and data were analyzed using ANOVA. Results: The study results showed that organic red rice had a lower yield, but higher dietary fiber and resistant starch content compared to non-organic red rice. In contrast, the moisture content was relatively similar between the two types of red rice. Kembang goyang snacks made with the addition of organic or non-organic red rice flour had higher dietary fiber content compared to the control. However, increasing the amount of organic or non-organic red rice flour in various ratios resulted in similar toughness to the commercial product. Conclusions: The best formulation of the kembang goyang snack was obtained at a 40:60 ratio of organic red rice flour and white rice flour. This best kembang goyang snack formula can be classified as a fiber-rich product because it has 6.30% dietary fiber content and 6.30% resistant starch content. Also, it has a similar texture to commercial products.